Study of spectrum and clinical profile of benign breast disease in the rural area: is there any change - Jawade, Kailash K.; Bande, Vaishali (International Surgery Journal, 2020)
Background: Recent understanding of pathophysiology and health awareness may have impact on spectrum of benign breast disease (BBD) in rural area. We have analyzed clinical data of 88 cases of BBD for spectrum and clinical profile to compare with present studies. Methods: Clinical records of 88 cases of BBD were reviewed for demographic details, clinical presentation, management and outcome. Recent literature related to BBD in rural area was searched using various search engines. Results of our study were compared with recent studies. Results: Fibroadenoma (FA) was most common condition followed by fibrocystic disease. BBD were common in third decade 46 (52.3%). Lump was present in 87 cases. Lump was painful in 45 (52.3%), and associated with fever in 15 (17.1%) cases. Fine needle aspiration cytology and ultrasound was done in 70 and 32 patients in which diagnostic accuracy with histopathology was seen in 69.7% and 56.2% respectively. Surgical treatment included lumpectomy, lump excision, mastectomy, drainage with debridement and axillary clearance. Three patients of breast tuberculosis were treated with 9 months AKT. When compared with recent studies, over all spectrum was same expect chronic abscess presenting as lump was more in our series. Conclusions: Our study revealed benign neoplasms, inflammatory condition and tumor like lesions in 43.1%, 14.6% and 13.8% cases respectively. FA was the most common lesion. BBD were common in third decade. Except the chronic mastitis, incidence of various types of benign lesions was comparable with those found in other studies. There is not much change in overall spectrum of benign breast disease.